2018
DOI: 10.1080/00223980.2018.1447433
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Predispositions to Violate or Obey Traffic Rules and the Mediating Role of Driving Styles

Abstract: Traffic law violations are the most important determinants of traffic accidents. This study examined the influence of drivers' ethical perspective on their traffic violations and the mediating role of driving styles in these relationships. A sample of 313 drivers participated in the study. Contrary to expectations, high ethical relativism was found to be associated with fewer aggressive traffic violations. This suggests that the informal normative system that parallels the official traffic regulations is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…These results confirm results of previously conducted studies (Trueloves, Freeman & Davey, 2019;Holman& Popusoi 2018;Xu, Li & Jiang, 2014;Mawanga and Ntayi, 2010), which revealed that social factors have a pivotal role in derivers' compliance with traffic rules and safety standards or their violation, and emphasized the importance of compliance with traffic rules and safety standards to be an essential part of the urban culture in order to reduce traffic accidents (Mawanga & Jntayi, 2010). Therefore, the present study emphasizes that family, school and community together can significantly contribute to the reduction of traffic accidents and will save millions of lives and billions of dollars every year if enlightenment on traffic accidents becomes a key part of daily activities as earlier studies also demonstrated (Lee & Al-Mansour, 2019;Penmetsa, & Pulugurtha, 2017;Yusuf, 2017).…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…These results confirm results of previously conducted studies (Trueloves, Freeman & Davey, 2019;Holman& Popusoi 2018;Xu, Li & Jiang, 2014;Mawanga and Ntayi, 2010), which revealed that social factors have a pivotal role in derivers' compliance with traffic rules and safety standards or their violation, and emphasized the importance of compliance with traffic rules and safety standards to be an essential part of the urban culture in order to reduce traffic accidents (Mawanga & Jntayi, 2010). Therefore, the present study emphasizes that family, school and community together can significantly contribute to the reduction of traffic accidents and will save millions of lives and billions of dollars every year if enlightenment on traffic accidents becomes a key part of daily activities as earlier studies also demonstrated (Lee & Al-Mansour, 2019;Penmetsa, & Pulugurtha, 2017;Yusuf, 2017).…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…This supports previous TPB studies (Conner et al, 2007;Elliot & Thomson, 2010), which further highlights the potential importance of moral norms for traffic behaviours. Nonetheless, depending on the types and motives of violation behaviours, people may interpret traffic violations as (non) normative actions (Havârneanu & Havârneanu, 2012), which may have important moral underpinnings (Holman & Popusoi, 2018). Further studies are needed to determine the extent to which a moral perspective relates to obedience to traffic rules.…”
Section: Discussionmentioning
confidence: 99%
“…stress) and intentions. While moral norms are expected to have an important influence on the drivers' choice to obey or transgress the rules (Holman & Popusoi, 2018), findings suggest that stress appears to directly affect moral reasoning (Starcke et al, 2011;Youssef et al, 2012). For example, in a series of experimental studies, Shalvi et al (2012) found that individuals under stressful conditions (i.e.…”
Section: Psychological Stressors and Traffic Violationmentioning
confidence: 99%
“…At the international level, it is common knowledge that drivers violate traffic rules [11][12][13]. What this report is model-based emphasis that perspectives of the road users determine the associated OHS behavior [11][12][13]; and can be used as predicting factor [14]. Given that knowledge is power, it implies that there is need to empower the people.…”
Section: Implication For Tackling Ohs Issues On the Roadsmentioning
confidence: 99%